A Systematic Review of Dropout From Psychotherapy for Posttraumatic Stress Disorder Among Iraq and Afghanistan Combat Veterans. Issue 5 (16th September 2015) - Goetter, Elizabeth M.; Bui, Eric; Ojserkis, Rebecca A.; Zakarian, Rebecca J.; Brendel, Rebecca Weintraub; Simon, Naomi M.
Abstract: A significant number of veterans of the conflicts in Iraq and Afghanistan have posttraumatic stress disorder (PTSD), yet underutilization of mental health treatment remains a significant problem. The purpose of this review was to summarize rates of dropout from outpatient, psychosocial PTSD interventions provided to U.S. Operation Iraqi Freedom (OIF), Operation Enduring Freedom (OEF), and Operation New Dawn (OND) veterans with combat‐related PTSD. There were 788 articles that were identified which yielded 20 studies involving 1, 191 individuals eligible for the review. The dropout rates in individual studies ranged from 5.0% to 78.2%, and the overall pooled dropout rate was 36%, 95% CI [26.20, 43.90]. The dropout rate differed marginally by study type (routine clinical care settings had higher dropout rates than clinical trials) and treatment format (group treatment had higher dropout rates than individual treatment), but not by whether comorbid substance dependence was excluded, by treatment modality (telemedicine vs. in‐person treatment), or treatment type (exposure therapy vs. nonexposure therapy). Dropout is a critical aspect of the problem of underutilization of care among OEF/OIF/OND veterans with combat‐related PTSD. Innovative strategies to enhance treatment retention are needed.